THE INFLUENCE OF CLUSTERING TECHNIQUE ON STUDENTS’ DESCRIPTIVE TEXT WRITING ABILITY AT SEVENTH GRADE OF MTS MUHAMMADIYAH PADANGPANJANG - Beniario, Gusmaizal Syandri Putri Rahayu. M (FKIP UMSB, 2022)
The purpose of this research is to investigate whether any significant influence of using clustering technique on students’ descriptive text writing ability at seventh grade of MTs Muhammadiyah Padangpanjang. The population of this research at the seventh grade of MTs Muhammadiyah Padangpanjang. The sample of this research was class seven which consisted of 34 students. The design of this research was pre-experimental research in one group design which divided into two stages consisting of pre-test and post-test in the learning process. Then, the instrument of this research was a writing test, to score the students’ descriptive text writing ability on pre-test and post-test the researcher used rubric assessment from Brown (2003). Furthermore, the success criteria were determined on the five indicators of writing namely content, organization, vocabulary, language use/grammar, and mechanics. The researcher analyzed the data by using statistical formulation and Microsoft Excel 2010 with 0,05 significance level. After analyzed the data, the result of the average post-test score is 80, increased from pre-test score is 60. Next, the value of tcount was higher than ttable. It can be seen from tcount is 12,98 > ttable is 2,035 at the significance level 0,05 and degree of freedom (df) = 33. It means that, the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. It can be concluded that, the use of clustering technique is giving significant influence to students’ descriptive text writing ability at seventh grade of MTs Muhammadiyah Padangpanjang. Key Words: Clustering Technique, Writing, and Descriptive Text.